Model Hubungan Hujan dan Runoff (Studi Lapangan) - deny arista agustianto (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
This research present the model study on the relation between rainfall pattern andÂ surface run off flows of a small catchment area. The influences of catchment area characteristics such as land use, soil behavior, topography condition and other related physical condition was investigated. Surface runoff flow and peak discharge assessment was done at each sub catchment area by using Rasional method. Application of this model was to make predictions about the large pattern and surface runoff flow discharge on the channel modeling that occurs due to rain. Results of studies that have been done on modeling the river flow showed that the variables that most influence was the runoff coefficient based on land use and rainfall patterns will affect other parameters such as the time the water flows from the catchment area to the drainage chanel modeling and drainage characteristic. Close agreement between model result and rasional method is shown on surface run off flow and peak discharge. This inaccuracy could be minimized not only by improving the model but also using a better data calibration, such as highly correlated rainfall and river discharge data with catchment area land use condition. Â Keywords : Rainfall, surface runoff, time of concentration, flow discharge, rasional method